Implementation of an Integrated Curriculum in Islamic Religious Education at SMAIT Abu Bakar Boarding School Kulon Progo Academic Year 2021/2022 - Noor Syahid; Abu Darda; Ella Nofianti (Educan : Jurnal Pendidikan Islam, 2022)
The large portion of religious education in Islamic Boarding School raises the problem that graduates are seen as not of the same quality as public schools. On the other hand, Islamic boarding schools have developed a lot of learning curricula, that the resulting students can master general science and religion, one of which is by implementing an integrated curriculum. Therefore, this research aims to describe the concept and the implementation of the integrated curriculum. This research used qualitative research with case study approach. The data collected from interviews, observation, and documentation. Data analysis used includes data collection, data reduction, data presentation, and verification. The result of this study are: (1) The concept used in SMAIT Abu Bakar Boarding School Kulon Progo  in the integrated curriculum is the concept of Integrated Islam and integrating 2013 Curriculum with Pesantren Curriculum. But the concept of the integrated Curriculum still has boundaries in its implementation. (2) The implementation of the integrated curriculum icludes planning, implementation and evaluation with supervision agenda. The conclusions are the curriculum concept in SMAIT Abu Bakar Boarding School Kulon Progo is the concept of Integrated Islam and the implemntation process is not much different from other curriculum. But in its implementation process, between one subject to another still has boundaries meanwhile as the theory used in this study, integrated curriculum eliminates boundaries between various subjects and presents the subject matter as a whole.